Steroid profile of porcine follicular fluid and blood serum: Relation with follicular development - Costermans, Natasja G. J. (Physiol Rep, 2019)
The aim of this study was to identify follicular fluid (FF) steroids which reflect follicular development in the early stages of the follicular phase and to establish whether the levels of these FF steroids correspond to their levels in serum. If these relations are established, serum steroid profiles may be used to monitor follicular development already in this early stage of the follicular phase. We used samples of two experiments, one with multiparous sows at the onset of the follicular phase (weaning) and one with primiparous sows at the midfollicular phase (48 hr after weaning). Complete steroid profiles were measured in pooled FF of the 15 largest follicles and serum using high‐performance liquid chromatography‐tandem mass spectrometry. In experiment 1, pooled FF volume, as a measure for average follicle size, tended to be positively related to higher FF 17β‐estradiol levels (β = 0.56, p = .08). In experiment 2, a larger FF volume was related not only to FF higher 17β‐estradiol levels (β = 2.11, p < .001) but also to higher levels of β‐nortestosterone (β = 1.15, p < .0001) and its metabolite 19‐norandrostenedione (β = 1.27, p < .01). In addition, FF volume was related to higher FF 17α‐OH‐pregnenolone (β = 1.63, p = .03) and 17α‐OH‐progesterone (β = 1.83, p < .001), which could indicate that CYP17,20‐lyase activity is limiting for 17β‐estradiol production in larger follicles at the beginning of the follicular phase. In serum, most of the steroids were present at lower levels compared to FF, except for the corticosteroids. Serum progestins and androgens were never related to follicle pool volume and steroid levels did not differ in the midfollicular phase compared to the onset of the follicular phase in the second experiment. Serum steroid levels therefore poorly reflect the developmental stage of the follicle pool in the first half of the follicular phase of the estrous cycle in sows.